Effectiveness of Exercise-based Interventions on Pelvic Floor Function in Postpartum Women: A Literature Review - Zimnoch-Włodarczyk, Aleksandra; Łapiński, Maciej; Zinko, Oksana; Napierała , Michał; Ciecierska, Kinga; Wasilkowska, Krystyna; Łatkowska, Sylwia; Jończy, Justyna (Quality in Sport, 2026)
Background. Pregnancy and childbirth are major risk factors for postpartum pelvic floor dysfunction, including urinary and anal incontinence and pelvic organ prolapse. Although pelvic floor muscle training (PFMT) is widely recommended as first-line management, its benefits appear predominantly short-term and functional. Aim. To synthesize evidence on the effectiveness and limitations of exercise-based interventions, particularly PFMT, in postpartum pelvic floor dysfunction. Materials and Methods. A structured literature review was conducted using PubMed and Google Scholar. Primary studies published between 2015 and 2025 involving postpartum women and evaluating PFMT, general exercise, or multimodal pelvic floor rehabilitation were included. Thirty-two studies were analyzed qualitatively. Results. PFMT consistently improved pelvic floor muscle strength and reduced urinary incontinence symptoms in the short term, particularly in symptomatic women. Targeted PFMT was more effective than general exercise. Evidence for anal incontinence was limited, and neuromuscular improvements rarely translated into meaningful continence outcomes. PFMT improved prolapse-related symptoms but did not induce anatomical improvement. Technology-assisted interventions improved adherence, while low-impact postpartum exercise appeared safe. Conclusions. PFMT is effective for short-term functional improvement in postpartum women but is insufficient as a stand-alone intervention for long-term continence outcomes or structural pelvic organ prolapse. Further research should focus on long-term follow-up and individualized, multimodal rehabilitation.